2014
DOI: 10.4137/aci.s13768
|View full text |Cite
|
Sign up to set email alerts
|

Spectrophotometric and Spectrofluorimetric Studies on Azilsartan Medoxomil and Chlorthalidone to Be Utilized in Their Determination in Pharmaceuticals

Abstract: The recently approved angiotensin II receptor blocker, azilsartan medoxomil (AZL), was determined spectrophotometrically and spectrofluorimetrically in its combination with chlorthalidone (CLT) in their combined dosage form. The UV-spectrophotometric technique depends on simultaneous measurement of the first derivative spectra for AZL and CLT at 286 and 257 nm, respectively, in methanol. The spectrofluorimetric technique depends on measurement of the fourth derivative of the synchronous spectra intensities of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…The standard addition technique was applied to evaluate the validity of the proposed methods ( Table 6). In bulk powder and commercial tablets, the results of the CHT and AZM determination were compared statistically with the reference first derivative spectra method [11] ( Table 7). "F" and "t" values were calculated, and they were found less than the tabulated ones apart from the case of PLS and PCR for CHT and AZM determination in commercial tablets (tand F-test values were higher than tabulated ones in case of AZM, and t value was higher than tabulated one in case of CHT).…”
Section: Ann and Ga-ann Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The standard addition technique was applied to evaluate the validity of the proposed methods ( Table 6). In bulk powder and commercial tablets, the results of the CHT and AZM determination were compared statistically with the reference first derivative spectra method [11] ( Table 7). "F" and "t" values were calculated, and they were found less than the tabulated ones apart from the case of PLS and PCR for CHT and AZM determination in commercial tablets (tand F-test values were higher than tabulated ones in case of AZM, and t value was higher than tabulated one in case of CHT).…”
Section: Ann and Ga-ann Methodsmentioning
confidence: 99%
“…Multivariate statistical models are very useful in spectral analysis because of simultaneous incorporation of multiple spectral intensities, which greatly improve the accuracy and potential applications of quantitative spectral analysis [10]. The literature survey showed that spectroscopic, RP-HPLC, and LC-MS methods [11,12] are reported for quantitation of AZM and CHT binary mixture. However, there is no reported method for the quantitation of the ternary mixture of AZM, CHT, and AZ may be because of the high similarity of UV spectra of AZM and AZ.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[19] Recently, Ebeid et al have developed a stability-indicating method for the combination of azilsartan medoxomil and chlorthalidone with its subsequent application to degradation kinetics. [20] However, no method has been reported for characterization of the degradation products formed under various stress conditions. Identification and characterization of degradation products is very important in the field of drug development.…”
mentioning
confidence: 99%
“…AZL in combination with chlorthalidone was also determined in dosage form using UV and fluorescence spectrophotometry [21], HPLC [22][23][24][25] and in human and rat plasma using LC/MS [26]. Fluorescence spectrometry is a very simple, rapid, efficient, selective, and highly sensitive technique for determination of drug in plasma [27][28][29].…”
Section: Introductionmentioning
confidence: 99%